Construction of Nitrogen‐Doped Biphasic Transition‐Metal Sulfide Nanosheet Electrode for Energy‐Efficient Hydrogen Production via Urea Electrolysis. Issue 17 (26th January 2023) - Xie, Hui; Feng, Yafei; He, Xiaoyue; Zhu, Yin; Li, Ziyun; Liu, Huanhuan; Zeng, Suyuan; Qian, Qizhu; Zhang, Genqiang
Abstract: Urea‐assisted hybrid water splitting is a promising technology for hydrogen (H2 ) production, but the lack of cost‐effective electrocatalysts hinders its extensive application. Herein, it is reported that Nitrogen‐doped Co9 S8 /Ni3 S2 hybrid nanosheet arrays on nickel foam (N‐Co9 S8 /Ni3 S2 /NF) can act as an active and robust bifunctional catalyst for both urea oxidation reaction (UOR) and hydrogen evolution reaction (HER), which could drive an ultrahigh current density of 400 mA cm −2 at a low working potential of 1.47 V versus RHE for UOR, and gives a low overpotential of 111 mV to reach 10 mA cm −2 toward HER. Further, a hybrid water electrolysis cell utilizing the synthesized N‐Co9 S8 /Ni3 S2 /NF electrode as both the cathode and anode displays a low cell voltage of 1.40 V to reach 10 mA cm −2, which can be powered by an AA battery with a nominal voltage of 1.5 V. The density functional theory (DFT) calculations decipher that N‐doped heterointerfaces can synergistically optimize Gibbs free energy of hydrogen and urea, thus accelerating the catalytic kinetics of HER and UOR. This work significantly advances the development of the promising cobalt–nickel‐based sulfide as a bifunctional electrocatalyst for energy‐saving electrolytic H2 production and urea‐rich innocent wastewater treatment. Abstract : Nitrigen‐doped Co9 S8 and Ni3 S2 hybrid nanosheet arrays on nickel foam (N‐Co9 S8 /Ni3 S2 /NF) are successfully synthesized by facile electrodeposition combined with an ammonification reaction, which exhibit superior and robust bifunctional electrocatalytic performance for urea oxidation reaction and hydrogen evolution reaction.